Plague risk in the western United States over seven decades of environmental change. (18th November 2021) - Carlson, Colin J.; Bevins, Sarah N.; Schmid, Boris V.
Abstract: After several pandemics over the last two millennia, the wildlife reservoirs of plague ( Yersinia pestis ) now persist around the world, including in the western United States. Routine surveillance in this region has generated comprehensive records of human cases and animal seroprevalence, creating a unique opportunity to test how plague reservoirs are responding to environmental change. Here, we test whether animal and human data suggest that plague reservoirs and spillover risk have shifted since 1950. To do so, we develop a new method for detecting the impact of climate change on infectious disease distributions, capable of disentangling long‐term trends (signal) and interannual variation in both weather and sampling (noise). We find that plague foci are associated with high‐elevation rodent communities, and soil biochemistry may play a key role in the geography of long‐term persistence. In addition, we find that human cases are concentrated only in a small subset of endemic areas, and that spillover events are driven by higher rodent species richness (the amplification hypothesis) and climatic anomalies (the trophic cascade hypothesis). Using our detection model, we find that due to the changing climate, rodent communities at high elevations have become more conducive to the establishment of plague reservoirs—with suitability increasing up to 40% in some places—and that spillover risk to humans at mid‐elevations has increased as well, although more gradually. These results highlight opportunities for deeper investigation of plague ecology, the value of integrative surveillance for infectious disease geography, and the need for further research into ongoing climate change impacts. Abstract : The impacts of climate change on human and wildlife health remain poorly understood. Carlson and colleagues develop a new method for reconstructing these impacts, and show that since 1950, environmental conditions in the western United States have become more favorable for plague ( Yersinia pestis ), including both its maintenance in wild mammals and spillover risk for humans.